2009
DOI: 10.1080/00016480902933056
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 expression in the guinea pig cochlea induced by intense noise stimulation

Abstract: Conclusion: These results suggest that noise induces free radical formation in the cochlea and that, in the guinea pig, heme oxygenase-1 (HO-1) may play an important role in the recovery from noise trauma in the organ of Corti. Objective: Free radicals are involved in noise-induced hearing loss. It has been demonstrated that the induction of HO-1 may protect cells exposed to oxidative challenge. The present study was designed to investigate the effect of intense noise exposure on HO-1 induction. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…Importantly, Yuan et al reported that noise-induced oxidative responses as indicated by products of lipid oxidation (4-hydroxynonenal) and protein nitration (3-nitrotyrosine) occurred in a noise-dose-dependent manner [82]. The results of this study are consistent with the literature in demonstrating that the levels of antioxidant enzymatic scavengers, including HO-1 and catalase, are increased in the cochlea (particularly the organ of Corti), in response to intense noise stimulation [83,84]. The natural defense system managed by antioxidant enzymatic scavengers seems to be overwhelmed by ROS accumulation, before or during initiation of TTS- or PTS-related damage.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, Yuan et al reported that noise-induced oxidative responses as indicated by products of lipid oxidation (4-hydroxynonenal) and protein nitration (3-nitrotyrosine) occurred in a noise-dose-dependent manner [82]. The results of this study are consistent with the literature in demonstrating that the levels of antioxidant enzymatic scavengers, including HO-1 and catalase, are increased in the cochlea (particularly the organ of Corti), in response to intense noise stimulation [83,84]. The natural defense system managed by antioxidant enzymatic scavengers seems to be overwhelmed by ROS accumulation, before or during initiation of TTS- or PTS-related damage.…”
Section: Discussionsupporting
confidence: 88%
“…HO-1 expression has been reported in cochlear hair cells and stria vascularis following a variety of stressors, including noise stress, heat stress, and pharmacological induction (Fairfield et al 2004;Lopez et al 2008;Kim et al 2009;Matsunobu et al 2009;Fetoni et al 2010). In the current study, CoPPIX treatment resulted in HO-1 induction primarily in resident macrophages without induction in hair cells or supporting cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that heat shock inhibits both cisplatin-and aminoglycoside-induced hair cell death (Cunningham and Brandon 2006). In addition to heat shock, noise exposure has also been shown to induce HSPs in the inner ear (Matsunobu et al 2009;Roy et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The preconditioning literature across systems and tissues further implicates antioxidants, TNFα, NFκB, HO-1, and Nrf2 (Dirnagl et al, 2003; Ran et al, 2005; Gidday, 2006; Lehotsky et al, 2009),. All the above factors are known to participate in cochlear responses to stress (Rybak, 2007; So et al, 2008; Matsunobu et al, 2009; Yamamoto et al, 2009; Chance et al, 2010), some to aminoglycosides specifically (Jiang et al, 2005; Chen et al, 2008; Taleb et al, 2009). The friend-or-foe nature of some factors, in particular TNFα and NFκB (Shi and Nuttall, 2007; Yamamoto et al, 2009), may depend on when and where they are expressed (Ohlemiller, 2008).…”
Section: Discussionmentioning
confidence: 99%